2006
DOI: 10.1111/j.1365-2109.2006.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oxolinic acid in black tiger shrimp, Penaeus monodon Fabricius, and the effect of cooking on residues

Abstract: This study examined the pharmacokinetics and bioavailability of oxolinic acid (OA) in black tiger shrimp Penaeus monodon Fabricius, in brackish water (salinity 10 g L À 1 ) at 28^29 1C, after intra-sinus (10 mg kg À1 ) and oral (50 mg kg À1 ) administration and also investigated the net changes of OA residues in the shrimp after cooking (boiling, baking and frying). The haemolymph concentrations of OA after intra-sinus dosing were best described by a two-compartment open model. The distribution and elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…). Pharmacokinetics in invertebrates has been performed to study the performance of antibiotics after their administration by different routes, including bath administration (Gore, Harm, Kukanich, Forsythe, Lewbart & Papich ; Uno, Aoki, Kleechaya, Ruangpan & Tanasomwang ; Faroongsarng, Chandumpai, Chiayvareesajja & Theapparat ). To our knowledge, this is the first pharmacokinetic study of a peptide administered by immersion baths in crustaceans.…”
Section: Discussionmentioning
confidence: 99%
“…). Pharmacokinetics in invertebrates has been performed to study the performance of antibiotics after their administration by different routes, including bath administration (Gore, Harm, Kukanich, Forsythe, Lewbart & Papich ; Uno, Aoki, Kleechaya, Ruangpan & Tanasomwang ; Faroongsarng, Chandumpai, Chiayvareesajja & Theapparat ). To our knowledge, this is the first pharmacokinetic study of a peptide administered by immersion baths in crustaceans.…”
Section: Discussionmentioning
confidence: 99%
“…The elimination half-life of OA from black tiger shrimp hemolymph was 17.7 h, which was almost half that found for kuruma shrimp (33.2 h). Uno et al [53] showed that a maximal hemolymph concentration of OA of 4.20 mg/ml was observed at 4 h after oral administration of 50 mg/kg body weight in back tiger shrimp, whereas it was 17.8 mg/ml at 7 h at the same dosing regime in kuruma shrimp [52]. These data indicate that the absorption rate in black tiger shrimp is more rapid than that in kuruma shrimp, whereas the extent of absorption in the former is lower than that in the latter.…”
Section: Antibiotic Residues In Penaeid Shrimpmentioning
confidence: 99%
“…The pharmacokinetic profile of OA has previously been extensively studied in finfish species, but there are few studies on the pharmacokinetics and residues of OA in penaeid shrimp [52,53]. Results from these studies indicated 932 Environ.…”
Section: Antibiotic Residues In Penaeid Shrimpmentioning
confidence: 99%
See 2 more Smart Citations